2022
DOI: 10.3390/catal12030261
|View full text |Cite
|
Sign up to set email alerts
|

High Selectivity Electrocatalysts for Oxygen Evolution Reaction and Anti-Chlorine Corrosion Strategies in Seawater Splitting

Abstract: Seawater is one of the most abundant and clean hydrogen atom resources on our planet, so hydrogen production from seawater splitting has notable advantages. Direct electrolysis of seawater would not be in competition with growing demands for pure water. Using green electricity generated from renewable sources (e.g., solar, tidal, and wind energies), the direct electrolytic splitting of seawater into hydrogen and oxygen is a potentially attractive technology under the framework of carbon-neutral energy producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 90 publications
0
30
0
Order By: Relevance
“…The difference between simulated and natural seawater is attributed to the greater concentrations of K + , Mg 2+ , Ca 2+ , and SO 4 2− . 5 Ji et al 53 showed that Mg 2+ can reduce significantly the H 2 evolution. These findings were supported by those of Li et al, 53 who showed that the chelation of Mg 2+ blocks the separation of photogenerated electron−hole excitons and induce charge redistribution, thereby negatively impacting on the photocatalytic performance.…”
Section: Confirmed That Increasing [V Omentioning
confidence: 99%
See 4 more Smart Citations
“…The difference between simulated and natural seawater is attributed to the greater concentrations of K + , Mg 2+ , Ca 2+ , and SO 4 2− . 5 Ji et al 53 showed that Mg 2+ can reduce significantly the H 2 evolution. These findings were supported by those of Li et al, 53 who showed that the chelation of Mg 2+ blocks the separation of photogenerated electron−hole excitons and induce charge redistribution, thereby negatively impacting on the photocatalytic performance.…”
Section: Confirmed That Increasing [V Omentioning
confidence: 99%
“…53,54 Another factor is the blockage of surface active sites by these ions as well as by suspended and dissolved species. 5 Solids suspended in seawater decrease light absorption by scattering and dissolved species may alter the refractive index and so increase reflection. These effects also can provide the energy to trigger biochemical reactions that can reduce the H 2 production as well.…”
Section: Confirmed That Increasing [V Omentioning
confidence: 99%
See 3 more Smart Citations